2008
DOI: 10.1093/hmg/ddn376
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in macrophage phenotypes and macrophage competition for arginine metabolism affect the severity of muscle pathology in muscular dystrophy

Abstract: Duchenne muscular dystrophy (DMD) is the most common, lethal, muscle-wasting disease of childhood. Previous investigations have shown that muscle macrophages may play an important role in promoting the pathology in the mdx mouse model of DMD. In the present study, we investigate the mechanism through which macrophages promote mdx dystrophy and assess whether the phenotype of the macrophages changes between the stage of peak muscle necrosis (4 weeks of age) and muscle regeneration (12 weeks). We find that 4-wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
465
0
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 443 publications
(498 citation statements)
references
References 60 publications
21
465
0
12
Order By: Relevance
“…Furthermore, a shift in macrophages polarization M1-M2 is observed from acute phase of 4-weeks to chronic stage, 12 weeks of age, where M2 macrophages are supposed to promote muscle repair by enhancing satellite cells proliferation. 50 These differences between acute and chronic mice could partially explain the differences observed after ONX-0914 treatment, however we showed that both stage of pathology will benefit from the treatment.…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, a shift in macrophages polarization M1-M2 is observed from acute phase of 4-weeks to chronic stage, 12 weeks of age, where M2 macrophages are supposed to promote muscle repair by enhancing satellite cells proliferation. 50 These differences between acute and chronic mice could partially explain the differences observed after ONX-0914 treatment, however we showed that both stage of pathology will benefit from the treatment.…”
Section: Discussionmentioning
confidence: 66%
“…11 Conversely, chronic inflammation accompanying severe myopathies are responsible for secondary damage promoting muscle degeneration and fibrosis. 12,13 Consequently, the intensity, duration and timeline of the inflammatory response as well as myeloid cell phenotype switches must strictly coordinate with tissue regeneration time-points for efficient repair.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo, un modèle de souris transgéniques, déficientes pour l'activation du facteur de transcription C/EBPb (CCAAT-enhancer-binding protein) chez lesquelles la transition des macrophages vers le phé-notype anti-inflammatoire est inhibée, a montré que le nettoyage des débris tissulaires n'est pas affecté en l'absence des macrophages anti-inflammatoires, mais que la différenciation des myoblastes et la croissance des fibres musculaires étaient déficientes [23]. Il est important de noter que les phases pro-et anti-inflammatoires peuvent se chevaucher, les différentes sous-populations de macrophages se retrouvant alors au même instant au niveau de la même zone régénérative [24,25]. Chez l'homme, il a été observé que les zones régénératives d'un muscle contenant des myoblastes prolifératifs, présentent préférentiellement des macrophages pro-inflammatoires.…”
Section: Résolution De L'inflammation Et Régénération Musculaireunclassified
“…Les macrophages, bien qu'essentiels à la réparation tissulaire lors d'une blessure aiguë, sont « désorganisés » dans ce type de blessure chronique. En effet, les macrophages pro-inflammatoires qui demeurent normalement actifs quelques jours à la suite d'une blessure aiguë, sont présents de façon chronique dans les muscles dystrophiques ce qui limite leur changement de phénotype vers un profil anti-inflammatoire qui est l'acteur de la réparation musculaire [24]. Cette présence prolongée des macrophages pro-inflammatoires est à l'origine des effets myotoxiques [24].…”
Section: Vieillissementunclassified
See 1 more Smart Citation